Upaya Meningkatkan Minat Belajar Kelas V SDN Socah 1 dengan Media Pembelajaran IPA Berbasis Powtoon - Julia Ayu Puspita; Agung Setyawan (Pusat Riset dan Inovasi Nasional, 2023)
Technological developments are increasing rapidly in the world of education, therefore human skills must also go hand in hand with these technological developments. But besides that, there are also educators or teachers who have not taken advantage of the sophistication of this technology, so that it can also affect student learning interest. So that it requires a memorable learning process that is interesting and fun which aims to increase student learning interest. An example of an interesting and fun learning media is the powtoon learning media, which combines interesting audio, visual and animated media elements. So that in this study the aim was to find out whether there was an influence from the use of powtoon learning media on learning interest in fifth grade students at SDN Socah 1. The type of research used by researchers was a type of qualitative research, with descriptive quantitative and descriptive qualitative data analysis methods, in this study also used interview techniques, tests, observation, and documentation for data collection. Then the results will show that the powtoon-based learning media has the effect of increasing students' interest in learning, especially in science subjects, because it is considered interesting and fun so that capturing material is easy to understand.